1994
DOI: 10.1111/j.1476-5381.1994.tb14752.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide‐dependent release of vasodilator quantities of calcitonin gene‐related peptide from capsaicin‐sensitive nerves in rabbit skin

Abstract: 1 Calcitonin gene-related peptide (CGRP) is a potent and long lasting vasodilator in the cutaneous microvasculature of many species including the rabbit. In this study we have investigated the role of nitric oxide in the release of endogenous CGRP, in response to capsaicin, in rabbit skin.2 Cutaneous blood flow was measured in response to intradermally-injected agents by a multiple site '33Xenon clearance technique. 3 The increased blood flow induced by capsaicin (100 nmol/site) and CGRP (3 pmol/site) was tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 43 publications
7
45
0
Order By: Relevance
“…In vivo experiments using a rat model of endotoxicosis have shown that the early hypotension and the loss of vascular responsiveness to noradrenaline occurring within the first 1 h of shock was dependent on NO production and apparently involved the activation of cNOS in either endothelial or neural cells (Wright et al, 1992;Szabo et al, 1993). Some studies have shown that NO appears to increase CGRP release from perivascular nerves in cerebral arteries (Wei et al, 1992), and microvessels in skin (Holzer & Jocic, 1994;Hughes & Brain, 1994;Kajekar et al, 1995) by observation of blood flow in response to a CGRP receptor blocker. On the other hand, several studies have indicated that CGRP does not account for vasodilatation in response to NO (Ralevic et al, 1992;Ayajiki et al, 1994;Faraci & Breese, 1994;Brian et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo experiments using a rat model of endotoxicosis have shown that the early hypotension and the loss of vascular responsiveness to noradrenaline occurring within the first 1 h of shock was dependent on NO production and apparently involved the activation of cNOS in either endothelial or neural cells (Wright et al, 1992;Szabo et al, 1993). Some studies have shown that NO appears to increase CGRP release from perivascular nerves in cerebral arteries (Wei et al, 1992), and microvessels in skin (Holzer & Jocic, 1994;Hughes & Brain, 1994;Kajekar et al, 1995) by observation of blood flow in response to a CGRP receptor blocker. On the other hand, several studies have indicated that CGRP does not account for vasodilatation in response to NO (Ralevic et al, 1992;Ayajiki et al, 1994;Faraci & Breese, 1994;Brian et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, our results suggest that NO plays an important role in ocular inflammation and that in fact NO may have dual effects: first, NO is involved in the activation of C-fibres, causing release of transmitters such as CGRP; secondly, NO mediates the effects of CGRP (see also Andersson, 1992). Recently it was reported that L-NAME inhibited the capsaicin-induced (and C-fibre-mediated) increase in blood flow in rabbit skin, suggesting a role for NO in the activation of C-fibres (Hughes & Brain, 1994). Interestingly, NO has been found to accelerate the synthesis of prostaglandins which in turn may cooperate with NO in activating C-fibres (Sautebin et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is particularly interesting because there is much debate surrounding the role of NO in the vasodilator mechanism of CGRP. If one considers endogenous CGRP release from capsaicin-sensitive nociceptors in the skin pivotal for the capsaicin-induced DBF response and one takes into account that the vasodilator effect of CGRP in humans is partly mediated by the release of NO (de Hoon et al, 2003), one Hughes and Brain (1994) demonstrated that in the rabbit cutaneous microvasculature, NO synthase inhibition had no effect on the subjects ϭ 11; number of observations after capsaicin/placebo per arm ϭ 22) during intra-arterial infusion of indomethacin (5 g ⅐ min Ϫ1 ⅐ dl Ϫ1 forearm). DBF increase was similar in the indomethacin IA and the NIA after application of 1000 g of capsaicin.…”
Section: Mediators Of Capsaicin-induced Dermal Vasodilation 251mentioning
confidence: 99%